Manastir Morača - Todić, Branislav 1952- (Beograd Balkanološki Institut SANU, 2006)
Zsfassung teilw. in engl., teilw. in franz. Sprache
In kyrill. Schr., serb. - Mit engl. Zsfassungen
In kyrill. Schr., serb.
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Morača (Monastery); Mural painting and decoration -- Montenegro -- Morača River Region; Icons -- Montenegro -- Morača River Region; Christian art and symbolism -- Montenegro -- Morača River Region; Aufsatzsammlung